The Norton anthology of theory and criticism - Leitch, Vincent B. (W. W. Norton, 2001)
"The Norton Anthology of Theory and Criticism, Third Edition, is a comprehensive collection of work relating to literary theory from major philosophers ranging from Plato to Mary Anne Warren. These works-selected from a wide geographical, chronological, and thematic range-have been curated and edited into a readable foundational text for students and instructors alike to use"--